Largest of maximum (LOM) method for switching fuzzy control system - Perumal L.; Nagi F.H. (Institution of Engineers (Australia), 2023)
Switching control systems are inexpensive and provide signals to activate or deactivate the system actuators. In this paper, fuzzy logic controllers, which produce switching signals have been developed using largest of maximum (LOM) defuzzification method. Two control schemes of two-level and three-level outputs are described here as bang-bang and bang-off-bang respectively. Comparison between the centroid defuzzification method and LOM defuzzification method shows that the latter is suitable method to yield switching signals. Gain scheduling technique is applied further to the controllers using LOM defuzzification to obtain lowest settling time. Both control schemes (bang-bang and bang-off-bang) are simulated in Matlab-Simulink environment for attitude control of one axis satellite system. Comparison between the two shows that bang-bang system with gain scheduling technique outperforms the bang-off-bang controller. Institution of Engineers Australia, 2008.